Pulmonary sequestration mimicking lung cancer – A case report - Adzić, Tatjana N.; Radovanović, Dragan V.; Aćimović, Bojana D.; Popović, Marko P. (Vojnosanitetski pregled, 2017)
Introduction. Pulmonary sequestration is a rare congenital anomaly and most intralobar sequestrations were located in lower lobes. Case report. We reported an unusual 28-year-old female patient with intralobar pulmonary sequestration on the left lower lobe, successfully treated with lobectomy. Computed tomography (CT) of the chest with intravenous contrast revealed multiple clustered cystic lesions in the left lower lobe with aberrant artery from descedenting aorta. Additional aortography showed an aberrant artery (3 mm in diameter) arising from the abdominal aorta and flowing into the lesion. Conclusion. Standard therapy regimen for pulmonary sequestration includes surgery. CT scan of thorax with intravenous contrast and aortography represent the gold standard for its diagnosis. Tumor-like shadows seen on the chest radiography or CT scans should not be always suspected on malignant lesions.